KONDISI MODAL SOSIAL DALAM USAHA PEMBERDAYAAN MASYARAKAT PETANI TEMBAKAU (Studi Kasus di Kecamatan Mojosongo Kabupaten Boyolali) - Soebandriyo Soebandriyo (JURNAL LITBANG PROVINSI JAWA TENGAH, 2013)
This study was conducted with the location in the District Mojosongo Boyolali, type a descriptive qualitative research, while informants: Village, Extension field, and tobacco farmers. Objective: To determine the context of social capital in an effort to strengthen community empowerment in the District Mojosongo Boyolali, to determine the condition of social capital in the business community empowerment in the District Mojosongo tobacco farmers. Results: Tobacco Farmers in Sub Mojosongo less active in group activities that have been determined by mutual agreement between tobacco farmers with extension, if invited at the regular meeting of community groups tobacco farmers, field workers, most have never been able to attend, this is because most of the tobacco farmers raising dairy cattle, there is no trust of the other group members, and no information obtained from other group members, the activities of the tobacco farmer groups further improved, and more active in activities, namely through the invitation if there is a regular meeting of farmers groups tobacco are expected to attend, as the meeting of members of a group of tobacco farmers will earn the trust of the other group members as well as to obtain information that is very important for members of the group of tobacco farmers, and ultimately believed by members of the other group, where the information can be opened with a network of financial institutions and banks, as well as with existing cigarette factory, group meetings and activities carried out at night, with the socialization of the field to a group of farmers, assistance provided with infrastructure such as water pumps, hand pump sprayers pests, leaf cutter knife.